Pariwisata Kerta Masa: Gagasan Alternatif Kebijakan Pembangunan Pariwisata Bali - Anak Agung Gede Duwira Hadi Santosa; Luh Ayu Nadira Saraswati (University of Udayana, 2020)
Kerta Masa is a noble value that is passed down across generations and lives in Balinese society. Carrying the spirit of order, tranquility, togetherness, harmony, and prosperity, the concept of Kerta Masa can be applied more broadly as a basis for quality and sustainable tourism development policies in Bali Province, in which the tourism direction development policies currently tends to be quantity oriented.